Investigating the migration law of aggregates during concrete flowing in pipe. (10th August 2020) - Liu, Guoming; Guo, Xiaohan; Cheng, Weimin; Chen, Lianjun; Cui, Xiangfei
Highlights: Migration characteristic of particles was investigated in concrete flow. Factors that affect particle migration were explored. Effect of particle shape on particle migration was investigated. Flow induced particle migration was discussed based on shear, gravity and wall effect. Abstract: During pumping fresh concrete pipes, aggregate migration is occurred under the action of various forces. In order to study the migration characteristic of aggregates during concrete flowing in pipes, in this paper, we built the test system based on particle tracking technology. Transparent concrete was prepared. The particle capture function of high-speed camera was used to track particle motion. Results showed that the radial displacement of particles depended on the initial location and aggregate size. Small aggregates near pipe wall or center axis had fewer motion. For the particles with larger diameter, the migration direction almost pointed to the axis of pipe. The migration displacement of nature aggregates was smaller than that of ground grinding ball. The migration displacement firstly increased and then decreased with increasing the diameter of particle. Moreover, the effect of particle shape on migration was explored. Finally, the wall effect, gravity induced particle migration and shear induced particle migration were compared based on the phenomenon of flow induced particle migration, results showed that the phenomenon of shear induced particle migration played the main role in the formation of lubrication layer. This study was of great significance to reveal the transport law of dense particle flow in the pipeline.